2009
DOI: 10.1101/gad.1820009
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor choice in the Hippo signaling pathway: homothorax and yorkie regulation of the microRNA bantam in the progenitor domain of the Drosophila eye imaginal disc

Abstract: The accurate control of cell proliferation and survival is critical for animal development. The Hippo tumor suppressor pathway regulates both of these parameters by controlling the nuclear availability of the transcriptional coactivator Yorkie (Yki), which regulates downstream target genes together with Scalloped (Sd), a DNA-binding protein. Here we provide evidence that Yki can also regulate target genes in conjunction with Homothorax (Hth) and Teashirt (Tsh), two DNA-binding transcription factors expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
254
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(266 citation statements)
references
References 59 publications
11
254
0
1
Order By: Relevance
“…Several transcription factors have been shown to control tissue growth in conjunction with Yki but how these proteins regulate transcription is still unclear. [15][16][17][18] What is better defined is the mechanism by which Yki activity is regulated by the SWH pathway; Wts/LATS1/2-mediated phosphorylation of Yki/YAP results in 14-3-3-dependent cytoplasmic sequestration of Yki/YAP, thus preventing Yki/ YAP activity in the nucleus. 3 To investigate whether Wbp2 affected Yki by influencing SWH pathway-mediated repression, we determined whether Wbp2 influenced Wts-dependent phosphorylation of Yki in S2 cells using anti-phospho-Yki-S168 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transcription factors have been shown to control tissue growth in conjunction with Yki but how these proteins regulate transcription is still unclear. [15][16][17][18] What is better defined is the mechanism by which Yki activity is regulated by the SWH pathway; Wts/LATS1/2-mediated phosphorylation of Yki/YAP results in 14-3-3-dependent cytoplasmic sequestration of Yki/YAP, thus preventing Yki/ YAP activity in the nucleus. 3 To investigate whether Wbp2 affected Yki by influencing SWH pathway-mediated repression, we determined whether Wbp2 influenced Wts-dependent phosphorylation of Yki in S2 cells using anti-phospho-Yki-S168 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…14 Yki drives a growth-regulatory transcriptional programme by regulating transcription factors that include Scalloped (Sd), [15][16][17] Homothorax (Hth) and Teashirt (Tsh). 18 Yki and YAP bind via a region of B100 amino acids in their N-termini to Sd and TEAD1-4, respectively. 15,19 Additional transcription factors have been shown to be activated by YAP including pEBP2a, ErbB-4 and p73, and these factors bind to the WW domains of YAP via PPxY (PY) motifs.…”
mentioning
confidence: 99%
“…The complexity of bantam control also highlights differential transcription factor interactions with Yorkie in growth control. While the TEAD family transcription factor Scalloped functions with Yorkie to regulate growth in the wing, recent studies have shown that the TALE family transcription factor Homothorax, together with the Zn finger transcription factor Teashirt, function with Yorkie to regulate growth in the fly eye disc 78 .…”
Section: Bountiful Crosstalk In the Hippo Pathwaymentioning
confidence: 99%
“…Phosphorylation of Yki results in its retention in the cytoplasm, thus blocking its transcriptional activity. 9 When Hippo signaling is inactive, Yki localizes to the nucleus where it forms complexes with transcription factors such as Scalloped, [10][11][12] Homothorax 13 or Mad 14 to activate the expression of target genes that promote cell growth, survival and proliferation. 15 Yki therefore acts as a growth promoter, whereas Hpo, Wts, Mats and Sav are considered tumor suppressors.…”
mentioning
confidence: 99%